Reparations and war : finding balance in repairing the past - Moffett, Luke (Oxford : Oxford University Press, 2023)
For thousands of years, reparations have been used to alleviate the devastating consequences of war. More recently, human rights law has established that victims have a right to reparations. Yet, in the face of conflicts that last for decades with millions of victims, how feasible it is to deliver reparations? And what are the obstacles?
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 27, 2023).
Keywords: War reparations; War victims; Politics and Government; International law